Newsmaking Practices in Uganda: A Comparative Framing Analysis of Two Leading Newspapers - Semujju, Brian (Newsmaking Cultures in Africa, 2018)
Studies on newsmaking cultures in general identify Media routines and norms, Organisational influences and several other factors as the major influences on newsroom behaviour. However, there has been research from the global South arguing that the above mainstream influences alone cannot explain how journalists deal with the news in countries such as Zimbabwe, Kenya and Tanzania, due to differences unique only to such countries. This chapter analyses content published about Uganda’s Electoral Commission in two newspapers (New Vision and Daily Monitor) to understand the newsmaking practices of Uganda’s press with the aim of situating the country’s newsmaking culture within or outside of the above-established factors. This, in addition, is intended to show the realities that create a climate for such newsroom behaviour. The chapter uses a combination of content analysis, key informant interviews and framing theory to explore and reflect the findings respectively.